2012
DOI: 10.1111/j.1467-9841.2011.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Transnational South Korea as a site for a sociolinguistics of globalization: Markets, timescales, neoliberalism1

Abstract: This special issue seeks a new direction for the sociolinguistics of globalization in the process of transnationalism, using as a case study new modes of Korean migration that are changing the face of Korean transnationalism, including short‐term early study abroad and return migration. Through a discussion of the historical and sociolinguistic context of South Korea, this paper demonstrates how transnational Korea is a relevant site for refining, reframing, and reconsidering the current sociolinguistics of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…South Korea is one of the countries responding to globalization with enthusiasm by underscoring the role of English in the process of globalization (Park, 2009;Park & Lo, 2012). For example, the government emphasized English as a global language through its national globalization project in the late 1990s, which led to implementing English as an official subject in elementary school.…”
Section: Globalization and English Teaching In South Koreamentioning
confidence: 99%
See 2 more Smart Citations
“…South Korea is one of the countries responding to globalization with enthusiasm by underscoring the role of English in the process of globalization (Park, 2009;Park & Lo, 2012). For example, the government emphasized English as a global language through its national globalization project in the late 1990s, which led to implementing English as an official subject in elementary school.…”
Section: Globalization and English Teaching In South Koreamentioning
confidence: 99%
“…One recent phenomenon relevant to the shifting teaching context in Korea is young Korean children's early study abroad (ESA) before college to learn English through early immersion in an English-dominant country (see Park & Lo, 2012). This ESA phenomenon is considered to be a middle-class Korean families' strategy to secure English as global linguistic capital for their children's competitiveness and belongingness in the global market (Park & Lo, 2012;Shin, 2014;Song, 2012).…”
Section: Globalization and English Teaching In South Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…Park and Lo 2012). In my ethnographic study on Korean ESA students attending Toronto high schools (Shin 2010), the students reported that contrary to their initial assumption that English will naturally improve in an English-speaking nation, their access to authentic English had been constrained for reasons relating to discrimination and sanctions experienced in the local context through racial and linguistic stigmatisation (e.g.…”
Section: The Globalised New Economy 'Authentic' English and Esamentioning
confidence: 91%
“…Over the past decade, ESA has established itself as an increasingly fundamental experience in middle-class urban Korean life (cf. Park and Lo 2012). For example, the number of ESA students who left Korea on student visas in 2006 was 45% greater than the previous year, with particularly explosive growth (69.5%) for elementary school students (KEDI 2007).…”
Section: The Globalised New Economy 'Authentic' English and Esamentioning
confidence: 96%